2016
DOI: 10.1155/2016/9621925
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Image Quality on Mobile Phones with Different Screen Resolution

Abstract: The diverse display screen imposes significant challenges for assessing the perceptual media quality across different mobile devices. In this paper, the perceived image quality on different mobile phones is investigated. Firstly, subjective experiments for image quality evaluation are implemented on 9 popular mobile phones and a broadcast-quality monitor to evaluate the impact on perceived image quality regarding the screen resolution, screen size, image resolution, and image coding quality. Furthermore, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…[10], [22] DA6 Being satisfied with my smartphone's aesthetics makes me want to use it more frequently.…”
Section: Li8mentioning
confidence: 99%
“…[10], [22] DA6 Being satisfied with my smartphone's aesthetics makes me want to use it more frequently.…”
Section: Li8mentioning
confidence: 99%
“…Popular resolutions of the time of these studies were 320p or 480p, which rarely appear on contemporary mobile devices. In an effort to investigate the same issue on screens larger than 5.7 inches and resolutions of 1440p (2K) or 2160p (4K), a recent subjective study [60] focused on more recent mobile devices having larger resolutions and screen sizes. The contents viewed by the subjects were re-scaled to 4K.…”
Section: E Mobile Devicesmentioning
confidence: 99%
“…Furthermore, the study by Lischke et al [12] included, in addition to text, comparisons between images and video quality assessment and concluded that the three tasks have significantly different requirements in terms of pixel density. Additionally, considering specifically the video signal, other studies [13], [14] analyzed the assessment of video sequences including the possibility that the mobile device and the size of the screen may have some influence. Furthermore, the works by Ou et al [15], and Laghari et al [16] examined the influence of video characteristics and format in the user QoE, with a huge statistical analysis based on subjective assessment.…”
Section: Related Workmentioning
confidence: 99%